Design and development of a simple device for clearing and cleaning municipal drainage system / Izran Tugiran - Tugiran, Izran (2009)
The drainage clean-up operation carried by the Local Municipality is manual. Very often the collect-ed materials are left close to the drain. Inevitably they are pushed back into the drain defeating the very purpose of cleaning and clearing. This project aims at developing a simple mechanism of clean-ing and clearing drains and delivering the collected material. The device is low cost (economic) and can reduce human labour.